The Effect of Self-assessment on the Development of EFL Reading Comprehension Skills - Kenza TAKARROUCHT (Universitas Bengkulu, 2021)
Using self-assessment as part of reading courses is key to improving reading comprehension skills. This study aims at exploring how self-assessment develops EFL students’ reading comprehension skills. It was conducted with a sample of 40 students enrolled in the English Department, University of Algiers 2 during the first semester of the academic year 2020/2021. To collect data, an embedded mixed-methods research paradigm was used which involved collecting both quantitative and qualitative data. The quantitative data were test scores collected as part of a pre-experiment. The pre-experiment involved administering a pre and post reading test and implementing a treatment. The treatment implemented was a self-assessment of reading strategies checklist. The qualitative data were obtained by means of an open-ended interview on participants’ reading strategies. Quantitative data were analysed by calculating the mean score and the t-test, while qualitative data were analysed using content analysis. The findings indicated that self-assessment helped the students to increase test scores and to develop their reading strategies. It enabled them to plan, monitor, and evaluate their reading process by implementing different strategies and techniques. Drawing on these findings, it is suggested that English teachers use self-assessment of reading strategies as part of reading courses, since it can improve students’ reading comprehension skills and strategy use.